The Effect of Perceived Usability and Perceived Convenience on User Satisfaction of Khanza Hospital Management Information System - Dhiana Wijayanti; Bambang Setya Budi I (Syntax Literate, 2022)
This study examines the effect of perceived usability and convenience on user satisfaction with management information systems in Khanza user hospitals. The population studied was hospital employees who used the khanza information system. The sampling technique in this study uses a non-probability sampling approach, namely by purposive sampling. This study used primary data sources. The data collection technique used is a questionnaire. The data analysis techniques used are descriptive analysis and multiple regression analysis. The theory used is the Technology Accepted Model. The results showed that the perception of usability and convenience significantly affected the satisfaction of information system users in hospital employees.